Demographic characteristics, behavioral problems, andiq profileof children with dyslexia at dyslexia association of indonesia from january-june 2019: a quantitative study - Rachmawati, Irma; Dewi Soegondo, Kristiantini; Solek, Purboyo (Jurnal Pendidikan Bitara UPSI, 2019)
One of the most frequent causes of learning difficulties in children is dyslexia. Dyslexia Association of Indonesia as a center of diagnostic and intervention of children with dyslexia has served more than 800 cases since 2005. However, studies on dyslexia in Indonesia were still very few comparing to the extent of the problem which need solutions. The study was conducted to know the demographic characteristics, behavioral problems, and IQ profile of children with dyslexia during the study period. Data were collected from medical record. There were 133 children with dyslexiaadministered in the study and dominantly male (76%). Most of them were diagnosed at the age of 4-6 year old (56.5%) and 7-9 year old (33.8%) with median age of diagnosis at 79months. About 49.6% were primary school students and 39.9% were preschoolers. Result showed that 3% of children have mild dyslexia, 33% have moderate dyslexia, 42% have severe dyslexia, 13% were at risk of dyslexia, and 9% have no severity defined, yet. Seventy nine children (60%) had comorbidities, among them 68.4% had dyscalculia and dysgraphia, 27.8% had dyspraxia, 24.1% with poor self-esteem and anxiety disorders, and 36.1% had behavioral problems (ADHD, conduct disorder, and oppositional defiant disorder). The IQ profiles (WISC, Griffith, or WPPSI) showed that 45.8% children had average IQ, 21.3% with superior IQ, 6.4% with very superior IQ, and 2.1% was gifted (FIQ median: 101.5). Gap were found between the VIQ and PIQ (median 14.5), whereby most children (69.2%) had VIQ less than their PIQ. These findings gave vivid picture to understand the IQ profile of dyslexic children and that dyslexia is not only about reading difficulties, but also includes comorbidities like behavioral problems that might cause academic problems despite progression of child’s reading ability.